Effectiveness of enhanced care for treatment of acute or persistent diarrhea in malnourished children aged 0 months to 10 years: a systematic review - Ridwa Alam; Khadija Vadsaria; Ahmad Khan; Uswa Jiwani; Aqsa Ishaq; Anmol Minaz; Ashraf Sharif; Yasir Bin Nisar; Jai K Das; Sajid Soofi; Shabina Ariff (Journal of Global Health Economics and Policy)
# Background Diarrhea poses a significant public health challenge, particularly affecting children under five. The link between malnutrition and diarrhea is well established, with diarrhea being a primary cause of malnutrition in young children and malnutrition exacerbating the severity of diarrhea. While the World Health Organization (WHO) recommends a comprehensive approach to both diarrhea and malnutrition management, including oral rehydration, continuous feeding, zinc supplementation, and antibiotics for specific strains, it does not adequately address the complex needs of malnourished children with diarrhea who may benefit from enhanced care in the form of follow-up and monitoring beyond initial treatment. We aimed to assess the effectiveness of enhanced care—defined as hospitalization, close clinical monitoring, or longer follow-up after completion of treatment—compared to WHO-defined standard care in improving clinical outcomes among malnourished children aged 0 to 10 years experiencing acute or persistent diarrhea.